RESPON APLIKASI ZPT ORGANIK PADA UMUR BIBIT YANG BERBEDA TERHADAP PERTUMBUHAN DAN PRODUKSI TOMAT CERI - Yunida berliana; Triara Juniarsih; Nina Unzila Angkat; Rizka Ismayanti (Prodi. Agroteknologi dan Perkebunan, Universitas Tjut Nyak Dhien, 2022)
Tomato is one of the favorite fruits consumed by the Indonesian people either consumed directly, as a salad or juiced and an additional ingredient in cooking ingredients. One type of tomato that is often consumed by the public is cherry tomatoes. Cherry tomatoes ( Solanum Lycopersicum var.. Cerasiforme) For this reason it is very important in improving production and high quality. This study used Organic ZPT and Different Seedling Ages. The design used by the Randomized Group Design (RAK) consisted of Seed Age Factors U1(15 days), U2(20 days) and U3 (25 days) and Dose Factors ZPTZ0 (without ZPT), Z1 (ZPT 50%), Z2 (ZPT 75%) and U3 (100%). The results of the Seed Age Research had a very noticeable effect on the Number of Branches at the age of 40 HST. Meanwhile, the results of ZPT have a very noticeable effect on Plant Height of 20 HST and Number of Branches of 40 HST. Meanwhile, the results of ZPT have a very noticeable effect on Plant Height of 20 HST and Number of Branches of 40 HST. And the interaction of the two had a noticeable effect on the number of branches ,the weight of the best crop fruit obtained at the U2Z1 treatment (20 days + 50% ZPT) which was 167.53 g.